2018
DOI: 10.20448/journal.522.2018.41.45.50
|View full text |Cite
|
Sign up to set email alerts
|

Home Field Advantage Calculation for Physical Education and Sport Students

Abstract: It is a well-established fact that playing at home field is an advantageous condition for professional sport teams. For this reason, the home field advantage in team sports is an important issue to be explored. It is also one of the different topics that physical education and sports students can use when they want to perform performance analysis on various sports branches in the future. The concept of home field advantage is determined by the ratio of the points the teams get from matches played at home field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Corporate governance also plays role in motivating managerial activities to achieve the goal of a company i.e. the maximization of firms" wealth (Cheung and Chan 2004;Inan, 2018).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Corporate governance also plays role in motivating managerial activities to achieve the goal of a company i.e. the maximization of firms" wealth (Cheung and Chan 2004;Inan, 2018).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Dowie was the first to apply the concept to soccer and came forward with three possible causes. He mentioned fatigue, familiarity and fans, however he did not reach clear-cut conclusions (3).…”
Section: Introductionmentioning
confidence: 96%
“…Some of this is probably because of lack of travel fatigue, rest may come from more balanced support. Seckin (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The study found that especially in Van, Rize and Diyarbakır, home advantage was higher than average, with Van having the most advantage (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The home field advantage is a key concept that has been studied across different sports for over a century. The first public attempt to statistically quantify the home field advantage was about 40 years ago (Inan, 2018), where Schwartz and Barsky (1977) studied the existence of home advantage in several sports and found that its effect was most pronounced in the indoor sports such as ice hockey and basketball. Since then, statisticians and psychologists have dug their heels into trying to map out this anomaly, and there is some consensus on it.…”
Section: Introductionmentioning
confidence: 99%